A Comparison between the Use of Cisco Packet Tracer and Graphical Network Simulator 3 as Learning Media on Students’ Achievement - Sari, Liska Mey Ika; Hatta, Puspanda; Wihidayat, Endar Suprih; Xiao, FENG (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Usually in studying the practice of computer networks, it is encountered several obstacles such as (1) limited computer networks design tools, (2) limited learning time to design computer networks and (3) technical difficulties for finding the solutions of errors. To overcome those barriers as proposed in this study, computer network simulators were used. Computer network simulators were expected to help students designing and simulating networks planned to be applied to computer network practices. This study used two simulators to compare its effectiveness in assisting the students to learn computer networks, which were Cisco Packet Tracer and Graphical Network Simulator 3 (GNS3). This study was aimed to determine the difference of the influence of network simulators to (1) learning achievement, and (2) learning achievement improvement. The quasi-experiment method was used and data were collected through conducting testing before and after the utilization of the simulators. Based on the testing results it was concluded that (1) different effect of using Cisco Packet Tracer and GNS3, the average grade achievement in the class using GNS3 and using Cisco packet tracer were 76.67 and 70 respectively, and (2) improved learning achievement using GNS3 for around 35%, higher than using Cisco Packet Tracer.